Temporal and developmental requirements for the Prader–Willi imprinting center - DuBose, Amanda J. (National Academy of Sciences, 2012)
Imprinted gene expression associated with Prader–Willi syndrome (PWS) and Angelman syndrome (AS) is controlled by two imprinting centers (ICs), the PWS-IC and the AS-IC. The PWS-IC operates in cis to activate transcription of genes that are expressed exclusively from the paternal allele. We have created a conditional allele of the PWS-IC to investigate its developmental activity. Deletion of the paternal PWS-IC in the embryo before implantation abolishes expression of the paternal-only genes in the neonatal brain. Surprisingly, deletion of the PWS-IC in early brain progenitors does not affect the subsequent imprinted status of PWS/AS genes in the newborn brain. These results indicate that the PWS-IC functions to protect the paternal epigenotype at the epiblast stage of development but is dispensable thereafter.